Door-to-balloon Time for ST-elevation MI in the Coronavirus Disease 2019 Era - Haytham Mously (Radcliffe Medical Media, 2021)
In patients presenting with ST-elevation MI, prompt primary coronary intervention is the preferred treatment modality. Several studies have described improved outcomes in patients with door-to-balloon (D2B) and symptom onset-to-balloon (OTB) times of less than 2 hours, but the specific implications of the coronavirus disease 2019 (COVID-19) pandemic on D2B and OTB times are not well-known. This review aims to evaluate the impact of COVID-19 on D2B time and elucidate both the factors that delay D2B time and strategies to improve D2B time in the contemporary era. The search was directed to identify articles discussing the significance of D2B times before and during COVID-19, from the initialization of the database to December 1, 2020. The majority of studies found that onset-of-symptom to hospital arrival time increased in the COVID-19 era, whereas D2B time and mortality were unchanged in some studies and increased in others.